Upregulation of bundle sheath electron transport capacity under limiting light in C4Setaria viridis. (7th May 2021) - Ermakova, Maria; Bellasio, Chandra; Fitzpatrick, Duncan; Furbank, Robert T.; Mamedov, Fikret; von Caemmerer, Susanne
SUMMARY: C4 photosynthesis is a biochemical pathway that operates across mesophyll and bundle sheath (BS) cells to increase CO2 concentration at the site of CO2 fixation. C4 plants benefit from high irradiance but their efficiency decreases under shade, causing a loss of productivity in crop canopies. We investigated shade acclimation responses of Setaria viridis, a model monocot of NADP‐dependent malic enzyme subtype, focussing on cell‐specific electron transport capacity. Plants grown under low light (LL) maintained CO2 assimilation rates similar to high light plants but had an increased chlorophyll and light‐harvesting‐protein content, predominantly in BS cells. Photosystem II (PSII) protein abundance, oxygen‐evolving activity and the PSII/PSI ratio were enhanced in LL BS cells, indicating a higher capacity for linear electron flow. Abundances of PSI, ATP synthase, Cytochrome b 6 f and the chloroplast NAD(P)H dehydrogenase complex, which constitute the BS cyclic electron flow machinery, were also increased in LL plants. A decline in PEP carboxylase activity in mesophyll cells and a consequent shortage of reducing power in BS chloroplasts were associated with a more oxidised plastoquinone pool in LL plants and the formation of PSII – light‐harvesting complex II supercomplexes with an increased oxygen evolution rate. Our results suggest that the supramolecular composition of PSII in BS cells is adjusted according to the redox state of the plastoquinone pool. This discovery contributes to the understanding of the acclimation of PSII activity in C4 plants and will support the development of strategies for crop improvement, including the engineering of C4 photosynthesis into C3 plants. Significance Statement: The efficiency of C4 photosynthesis decreases under low irradiance, causing a loss of productivity in crop canopies. We investigate shade acclimation of a model monocot of NADP‐dependent malic enzyme subtype, analysing cell‐specific protein expression and electron transport capacity. We demonstrate that C4 plants adjust the abundance and activity of Photosystem II in response to irradiance, specifically in bundle sheath cells.